2022
DOI: 10.1155/2022/2140895
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Deep Learning-Based Approach for Jazz Music Generation in MIDI Format

Abstract: In today’s real-world, estimation of the level of difficulty of the musical is part of very meaningful musical learning. A musical learner cannot learn without a defined precise estimation. This problem is not very basic but it is complicated up to some extent because of the subjectivity of the contents and the scarcity of the data. In this paper, a lightweight model that generates original music content using deep learning along with generating music based on a specific genre is proposed. The paper discusses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Figure 3.1 has articulated suggested model outcomes for various datasets. The data sets are "midi files dataset 1", "midi files dataset 2", and the "classical dataset" [12]. It is done by evaluating the dataset size in minutes, the numeral of ages vary, the period for each age in seconds, set size, initial losing value, and last losing worth.…”
Section: Results Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3.1 has articulated suggested model outcomes for various datasets. The data sets are "midi files dataset 1", "midi files dataset 2", and the "classical dataset" [12]. It is done by evaluating the dataset size in minutes, the numeral of ages vary, the period for each age in seconds, set size, initial losing value, and last losing worth.…”
Section: Results Analysismentioning
confidence: 99%
“…It has been found that "reinforcement learning-based algorithms" incorporated with sensor networks propose compelling opportunities for improving "music improvisation" and interpretation. Intelligent agents can comprehend and adapt their musical determination, resulting in more graphic and interactive music concerts in the IoT era, by leveraging real-time data from detectors [12].…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that previous research on MIDI music generation has primarily focused on well-known genres such as classical, jazz, and hip-hop [2,3]. As a result, the potential of MIDI music generation for creating music across a broader range of genres has not been fully explored or realized.…”
Section: Introductionmentioning
confidence: 99%